The influence of aboveground and belowground species composition on spatial turnover in nutrient pools in alpine grasslands. Issue 3 (14th December 2021) - Jing, Xin; Prager, Case M.; Chen, Litong; Chu, Haiyan; Gotelli, Nicholas J.; He, Jin‐Sheng; Shi, Yu; Yang, Teng; Zhu, Biao; Classen, Aimée T.; Sanders, Nathan J.
Abstract: Aim: An important research question in ecology is how climate and the biodiversity of aboveground plants and belowground microbiomes affect ecosystem functions such as nutrient pools. However, little is studied on the concurrent role of above‐ and belowground species composition in shaping the spatial distribution patterns of ecosystem functions across environmental gradients. Here, we investigated the relationships between the taxonomic composition of plants, soil bacteria and soil fungi and spatial turnover in nutrient pools, and assessed how species composition–nutrient pool relationships were mediated by contemporary climatic conditions. Location: Qinghai‐Tibetan Plateau. Time period: Current. Major taxa studied: Plants, soil bacteria and soil fungi. Methods: We surveyed plant assemblages, sampled the taxonomic composition of soil bacteria and soil fungi, and measured plant‐ and soil‐mediated nutrient pools at 60 alpine grasslands on the Qinghai‐Tibetan Plateau. Using Mantel tests, structural equation models and general linear models, we investigated the relative importance of the taxonomic composition of plant, soil bacterial, and soil fungal communities on the spatial turnover of alpine grassland nutrient pools. Results: We found that the taxonomic composition of plant, soil bacterial, and soil fungal communities was associated with local climate. However, the effects of local climate on the spatial turnover of plant‐ and soil‐mediated nutrient pools were mainly indirect and mediated through plant and soil bacterial species composition, but not through soil fungal species composition. We further found that the replacement component of soil bacterial β‐diversity and the richness difference of plant β‐diversity were the direct predictors of nutrient pools in the alpine grasslands. Main conclusions: These results highlight that belowground bacterial composition together with aboveground plant species composition are related to spatial turnover in nutrient pools, perhaps even driving it. Conserving above‐ and belowground biodiversity may therefore safeguard against the impacts of local climate on the functions of climate‐sensitive alpine grasslands.